PERAN OJK TERHADAP KERUGIAN NASABAH YANG DIAKIBATKAN OLEH MANAGER INVESTASI YANG TIDAK MEMILIKI IZIN - Pakpahan, Elvira Fitriyani; Winardi, Andres; Koharuddin, Jessica; Young, Karryn; Putri, Stela Dwi (LPPM STIH Awang Long, 2023)
This study examines the role of OJK in reducing unrecorded money losses for customers. The OJK’s responsibilities in regulating investment are divided into two parts, namely prevention aimed at non-customers, and taking action to overcome previous problems. Because this research is normative, it is based on documented legal theories, concepts, principles, and related laws and regulations. In this study, the main legal sources include Law no.8 of 1995 which regulates the capital market, and secondary legal sources are research in journals or publications related to the capital market. Document research is one of the methods used to obtain data. This study uses inductive and descriptive data. The results of this study are about the impact of OJK on the losses of unlicensed investment managers. Supervision activities include capital protection against customer losses, and the supervisory process for supervisory institutions.